(untitled) (The Research of Medical Science Review, 2025)
Objective: To observe the prevalence of HRS in decompensated cirrhosis patients suffering from spontaneous bacterial peritonitis. Study Design: A Cross sectional observational study Study Duration: 06 months Study Place: Tertiary Care Hospital, Lahore Methods: A cross-sectional observational study was conducted over six months in the Gastroenterology Department of a tertiary care hospital in Lahore. Using ICA criteria, HRS prevalence was assessed in 150 SBP patients. Data were analyzed using SPSS 25, with significance set at p<0.05. Ethical approval was obtained beforehand. Results: Out of 150 patients with SBP, 64 (42.7%) developed HRS—60.9% Type 1 and 39.1% Type 2. HRS patients had higher MELD scores (28.4 vs. 20.1), creatinine, bilirubin, and ALT levels. Median time to HRS onset was 4.2 days. Hospital mortality was significantly higher in HRS patients (53.1% vs. 18.2%; p<0.001). Hepatitis C was the leading cause of cirrhosis (51.5%). Conclusion: HRS significantly worsens outcomes in SBP patients, marked by higher mortality and rapid renal and hepatic deterioration. Early intervention with vasoconstrictors and albumin may improve survival.